A review on protein–protein interaction network of APE1/Ref‐1 and its associated biological functions. (19th March 2015) - Thakur, S.; Dhiman, M.; Tell, G.; Mantha, A. K.
<x xml:space="preserve">Abstract</x> Apurinic/apyrimidinic endonuclease 1 (APE1) is a classic example of functionally variable protein. Besides its well‐known role in (i) DNA repair of oxidative base damage, APE1 also plays a critical role in (ii) redox regulation of transcription factors controlling gene expression for cell survival pathways, for which it is also known as redox effector factor 1 (Ref‐1), and recent evidences advocates for (iii) coordinated control of other non‐canonical protein–protein interaction(s) responsible for significant biological functions in mammalian cells. The diverse functions of APE1 can be ascribed to its ability to interact with different protein partners, owing to the attainment of unfolded domains during evolution. Association of dysregulation of APE1 with various human pathologies, such as cancer, cardiovascular diseases and neurodegeneration, is attributable to its multifunctional nature, and this makes APE1 a potential therapeutic target. This review covers the important aspects of APE1 in terms of its significant protein–protein interaction(s), and this knowledge is required to understand the onset and development of human pathologies and to design or improve the strategies to target such interactions for treatment and management of various human diseases. Copyright © 2015 John Wiley & Sons, Ltd.